EU External Governance in Policy Area Under "Embedded Stalemate": Navigating the Dynamic Networks of Turkish Transport - ERTÜRK, AHMET CEMAL (Routledge Journals, Taylor & Francis Ltd., 2024)
This paper offers a nuanced examination of EU external governance within the challenging terrain of ‘embedded stalemate’, utilizing a network governance lens. Focusing on the Turkish transport sector as a case study, the research seeks to unravel the determinants of EU compliance in areas characterized by a protracted political impasse. By investigating the intricate dynamics of this ‘embedded stalemate’, the paper explores the question: ‘How do various factors influence the compliance with the EU in the Turkish transport sector amid a prolonged stalemate characterized by the absence of benchmarks and deadlines?’ Through 11 semi-structured interviews with key stakeholders, ranging from Turkish Ministry officials to private transport advisors, the study identifies variables such as incentives, actor capacities, asymmetry of interdependence, socialization, and politicization as crucial forces influencing the trajectory of compliance. The conceptual framework of network governance is introduced, providing a theoretical lens to understand the complex web of actors and preferences in this dynamic landscape. Therefore, the study concludes that as a result of ‘embedded stalemate’, patchy compliance is achieved through prolonged and dynamically evolving network governance involving a diverse array of actors from both the EU and Turkey sides.
Keywords: Compliance; Networkgovernance; Embeddedstalemate; Transport; Turkey